Contemporary Health Care and Nursing Education in Indonesia - Antigoni Fountouki; Fitri Yuliani; Hatifah Ihsanda; Tien Melati and Dimitris Theofanidis (Professor Despina Sapountzi-Krepia, 2024)
Contemporary Health Care and Nursing Education in Indonesia